A emergência do cartaz nas Jornadas de Junho: políticas e insurgências da escrita e da imagem em contexto de protesto - Rubens Rangel Silva (2021)
This research seeks to analyze the emergence of the poster in the June Journeys in different environments as an aesthetic-political exercise of self-expression and insurgent writing as an alternative to traditional media, as an articulating agent of visibility, thus constituting the political, didactic and transforming character of the event itself. Inspired by the collections and constellations, we built a research corpus that helped us to tell what happened in june 2013. From manifesto posters and other narratives about the June Journeys (journalistic, scientific and artistic) we sketched the complex relationships social and political aspects of that historical moment. To enlighten us in our analyses, we call on authors such as Rancière, Didi-Huberman, Deleuze, Brecht, Bakhtin, Butler, among others. The posters were analyzed in their performance next to the bodies of the demonstrators and in the environments where they appeared, being molded and molding these environments in the passage from one to the other. For the development of this study, in the exercise of building collections/constellations, we sought to organize and examine the posters/images of this thesis as a creative practice of communication in a given context and environments in which such contents were created. Our methodological model analyzed not only the set of images and posters we collected, but different sets of data that helped to understand the event. Different data sources were not treated as isolated fields. Instead, our model showed how different data related and complemented each other, giving a more complex and tangled view of events. The poster was a “device” of insurgency that interrupted the consensual machine in its usual way of producing meaning and legibility for the events. It allowed writing to become part of the performance and political gesture that redesigned urban paths and individual experiments. It allowed the subjects to experience and express their subjectivities. With this, we understand that it was not just a matter of elaborating understandings about the participation/exhibition in the protests, but of creating another experience, of inventing another vocabulary, presenting new terms, new statements that would oppose those already legitimized.